Effectiveness Of Dakon Media In Improving Numeracy Skills In Lower Grade Elementary School Students - Pinahayu, Pinasti; Prayogo, Ahmad Singgih (Prosiding University Research Colloquium, 2021)
The purpose of this study is to determine the effectiveness of the use of dakon media in improving numeracy skills in lower grade elementary school students. This research uses pre-experimental research method with one group pretest and posttest research design design. The subjects of this study were as many as 10 grade 1 elementary school students consisting of various schools. The research is divided into two cycles, namely before and after being given special treatment. The mean test result before treatment is 41 and the posttest test result gets 79 which results in the mean difference between pretest and posttest which is 38. Where there is a mean increase from the pretestt to the posttest. From the results of the study students showed an increase of pretest which only showed that as many as 90% of students were incomplete and only 10% of students completed. The student learning results in the posttest test showed an increase of 20% of students were incomplete and 80% of students completed.